THE EFFECTIVENESS OF FILTER MEDIA AND LIMNOCHARIS FLAVA ON PHYTOREMEDIATION OF LEACHATE - Sari, Ermina; Sari, Defita (Journal of Techno-Social, 2016)
This research aims to know the effectiveness of filter media and Limnocharis flava on the phytoremediation of leachate. This research was conducted in the greenhouse of Faculty Agriculture, University of Lancang Kuning on January-February 2015. The method used was experimental method by using a completely randomized design, which consists of 4 treatments with 5 replicates at each treatment. The parameters measured were turbidity, temperature, Total Suspended Solid, pH, and Dissolved Oxygen of leachate. Data were analyzed by using Analysis of Variance One-Way with significance level (Î±) = 0.01 and further tested by Duncan’s Multi Range Test. The results showed that there was a significant effect of filter media and Limnocharis flava on phytoremediation of leachate. Effective treatment to reduce levels of pollutants contained in the treatment 2 (Podzolik Merah Kuning, zeolites, Limnocharis flava) with effectiveness value were 87.09%, 4.8%, 91.81%, 21.93%, and (-)4680% for turbidity, temperature, Total Suspended Solid, pH, and Dissolved Oxygen respectively.